STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF BASIC PHYSICS PRACTICUM GUIDE ON MOBILE LEARNING - Darmaji Darmaji; Dwi Agus Kurniawan; Astalini Astalini; Utari Prisma Dewi (Ta'dib, 2020)
This study aims to investigate at students' perceptions on basic physics practicum guides on mobile learning. This research was a descriptive study involving 117 students with 59 physics education students and 58 chemistry ones. The instruments were questionnaires and semi-structured interviews intended to strengthen the quantitative data. The data collection was carried out by distributing questionnaire to the physics and chemistry education students who have conducted physics practicum using a mobile-based guide. Then interview was conducted only to those willing to be interviewed. The data were analyzed with  descriptive statistics to determine students' perceptions on mobile-based practicum guides.. The results showed that the practical learning guide based on mobile learning is feasible to use with the results of the perception of physics education included in both categories with a frequency of 38 (64.4%) and for chemical education perceptions also in the good category with a frequency of 28 (48.3%). The data were supported by interview results showing that students are more interested and enthusiastic in conducting practical work because they used mobile-based guides.